Clinicopathological study and management of salivary gland neoplasms in a tertiary care hospital - Bommareddy, Ratta Reddy; Gogineni, Raghuveer Chakravarthy; Adusumalli, Ramya Sai; Mallavarapu, David; Dunga, Swetha (International Surgery Journal, 2022)
Background: Salivary gland neoplasms are rare and constitute 3 to 4% of head and neck neoplasms. Majority of them are benign and a small percentage of them constitute malignant tumors. A careful clinical examination and judicious investigations help us to plan for an optimal surgical management. The aim of the study was to study clinico-epidemiological pattern, histological subtypes, management & postoperative complications of salivary gland neoplasms. Methods: This retrospective study was conducted on 52 patients admitted into the surgical wards of DR. PSIMS and RF during the period between November 2017 and October 2020. All the patients were followed up until one year (October 2021) after surgery. Results: Data of 52 cases of salivary gland neoplasms were recorded, of which 20 were male and 32 were female, and the median age group was 41 to 50 years. Majority of the patients (47) presented with swelling in the parotid region of 1 to 2 years duration. 44 patients were diagnosed with pleomorphic adenoma of the parotid gland and 43 of them underwent superficial parotidectomy. Conclusions: The parotid gland is the most commonly involved gland with the majority of the cases being pleomorphic adenoma. Superficial parotidectomy was the most common surgery done with a minimal complication rate.